Evolutionary change - patterns and processes - Francisco M. Salzano (Anais da Academia Brasileira de Ciências, 2005)
The present review considered: (a) the factors that conditioned the early transition from non-life to life;(b) genome structure and complexity in prokaryotes, eukaryotes, and organelles; (c) comparative humanchromosome genomics; and (d) the Brazilian contribution to some of these studies. Understanding thedialectical conflict between freedom and organization is fundamental to give meaning to the patterns andprocesses of organic evolution.